(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
Local history material can be used when studying a new topic in order to intensify the educational process, awaken interest in the topic, and broaden the horizons of students. Along with the increase in the intellectual level of children, the opportunity for extracurricular local history activities expands, and students themselves conduct local history work under the guidance of a teacher, which contributes to the development of independence, the desire for self-knowledge and self-improvement. At the same time, the volume, content and forms of local history activities depend on the age of the students, their level of knowledge and skills.